Poetic Judgment and the Music of the Spheres - Simmons, Joseph (Religion & literature, 2018)
The music of the spheres offers a picture for the situation of any human being who intuits an inescapable call to judgment which demands an unqualified response. The Christian paternoster, for example, responds with a model of prayerful common stewardship, while Immanuel Kant's epitaph responds with a model of individual philosophical mastery. These models implicitly claim something like the exemplarity often attributed to lyric poetry. This article argues, not that the paternoster or the epitaph is therefore a lyric poem, but rather that the contrast between these two ethical formulae can help us to understand the mode of exemplarity specific to the lyric utterance. To this end, it considers three celestial antiphons drawn from the tradition of British post-romanticism: Gerard Manley Hopkins's "Spelt from Sibyl's Leaves," William Butler Yeats's "The Cold Heaven" and Wystan Hugh Auden's "The More Loving One. " In varying ways, all three find both Christ's common fellowship and Kant's individual equality inadequate in the face of cosmic judgment. Hopkins's poem tensely suspends itself between mastery and stewardship; Yeats's violently renounces both; and Auden's eludes an explicit judgment on either. None of these three, however, offers an aesthetic alternative to the ethical model of Christ or Kant. If these postromantic lyrics are exemplary, it is only in their failure to be so; as readers we cannot, though we try, take their words as finally our own.